2020
DOI: 10.1152/ajprenal.00222.2020
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 contributes to renal ischemia-reperfusion injury by regulating Foxd1 methylation

Abstract: To investigate the mechanism of renal ischemia-reperfusion injury (IRI) via the regulation of N6-methyl-adenosine (m6A) and relevant genes, IRI was induced in Sprague Dawley rats and the urine and serum creatinine levels and tissue structure changes were observed. m6A and METTL3 protein levels were assessed via dot blotting and western blotting, respectively. The hypoxia/reoxygenation (H/R) cell model was constructed using NRK-52E cells, and METTL3 protein levels were assessed. METTL3 was inhibited to observe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…In mouse renal tubular epithelial cells, Mettl3 overexpression alleviated the colistin-induced renal injury by reducing apoptosis and enhancing the ability of antioxidative stress by the regulation of Nrf2, HO-1, and Keap1 . These results reflect those of Fanhang Meng et al who also found that suppressing Mettl3 could lead to the decreased expression of cleaved caspase-3, resulting in the reduction of NRK-52E cell apoptosis (Meng et al, 2020). On the contrary, knocking down the expression of Mettl3 could inhibit the viability, proliferation, and migration potential of HK2 cells and, thus, attenuate the TGF-β1-induced epithelial-mesenchymal transition (EMT), suggesting that Mettl3 might play a detrimental role in the process of renal fibrosis (Liu P. et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In mouse renal tubular epithelial cells, Mettl3 overexpression alleviated the colistin-induced renal injury by reducing apoptosis and enhancing the ability of antioxidative stress by the regulation of Nrf2, HO-1, and Keap1 . These results reflect those of Fanhang Meng et al who also found that suppressing Mettl3 could lead to the decreased expression of cleaved caspase-3, resulting in the reduction of NRK-52E cell apoptosis (Meng et al, 2020). On the contrary, knocking down the expression of Mettl3 could inhibit the viability, proliferation, and migration potential of HK2 cells and, thus, attenuate the TGF-β1-induced epithelial-mesenchymal transition (EMT), suggesting that Mettl3 might play a detrimental role in the process of renal fibrosis (Liu P. et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to Mettl3, the expression of Mettl14 was found to consistently increase in the kidney biopsies from patients with AKI, compared with those from patients with non-AKI . Moreover, loss of function of Mettl14 could mitigate the IRI-induced kidney injury through enhancing YAP1-TEAD signaling (Meng et al, 2020). Consistently, overexpression of Mettl14 was reported to significantly increase the expression of cleaved caspase-3 and promote apoptosis in HK2 cells with cisplatin treatment (Zhou P. et al, 2019).…”
Section: Discussionmentioning
confidence: 68%
“…Six Sprague-Dawley rats aged 6–8 weeks (200–250 g) were divided into two groups randomly using a random number table: The sham group and the AKI group. The IRI-induced AKI animal model was constructed by following the protocol of our previous study [ 18 ]. In brief, ischemia was induced by blocking the left renal vertebral arch and arteries for 45 min, and the removal of the right kidney.…”
Section: Methodsmentioning
confidence: 99%
“…NRK52E cells were purchased from Shanghai Cell Bank (Shanghai, China) and were cultured in Dulbecco’s modified Eagle’s medium supplemented with 5% fetal bovine serum (Gibco, Grand Island, NY, USA) and 50 units/mL penicillin/streptomycin (Gibco) at 37 °C in humidified air containing 5% CO 2 . The hypoxia-reoxygenation (H/R) cell model was constructed according to the protocol within a previous study [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study also showed that METTL3 is induced in ischemic/reperfusion (I/R)–induced AKI model. However, the validation of the function of METTL3 in vivo and analysis of the underlying mechanisms has not been performed ( 18 ).…”
Section: Introductionmentioning
confidence: 99%